Intergenerational differences in turnover intention of nurses: a cross-sectional survey in Jiangsu province, China - Guangyu Hu; Guangyu Hu; Zhen Wang; Chaoran Zhang; Jingwen Xu; Ziheng Shen; Lixin Peng; Haibo Xu; Haibo Xu (Frontiers in Psychiatry)
PurposeThis study aimed to learn the turnover intention of nurses in the workplace and analyze the influencing factors, commonalities, and differences from the perspective of intergenerational differences.MethodsBetween 4 September and 5 October 2023, a stratified cluster sampling was conducted among 2299 nurses at 16 tertiary hospitals in Jiangsu Province in China, using the questionnaire composited of General sociodemographic information, Work-Family Conflict Scale, Perceived Social Support Scale, Resilience Scale, and Turnover Intention Scale. SPSS v26.0 was performed to analyze data.ResultsA total of 2112 participants were included. The turnover intention of “Generation X” (born between 1965 and 1980) nurses was lower than that of “Generation Y” (born between 1981 and 1996) and “Generation Z” (born between 1997 and 2012). Work-family conflict was a common influencing factor on the turnover intention of three generations of nurses (P < 0.05). Family-work conflict (β = 0.099, P < 0.001), other support (β = -0.169, P < 0.001), resilience (β = -0.103, P < 0.001), night shifts (β = 0.047, P = 0.033), the number of children (β = -0.054, P = 0.041) and occupational diseases (β = -0.108, P < 0.001) were specific influencing factors of turnover intention among “Generation Y” nurses. Resilience (β= -0.172, P = 0.001) and family support (β = -0.188, P = 0.001) were specific factors of turnover intention in “Generation Z” nurses.ConclusionThis study reveals the intergenerational differences in the turnover intention of nurses and its influencing factors. The turnover intention of “Generation Y” and “Generation Z” nurses is higher than that of “Generation X”, and work-family conflict is the common factor of their turnover intention. It is suggested that hospital managers formulate targeted intervention strategies to reduce turnover intention according to the intergenerational characteristics of nurses.